Wideband reciprocity tunable electromagnetically induced transparency in complementary graphene metasurface. (26th March 2019) - Ning, Renxia; Bao, Jie; Meng, Yunji; Chen, Zhenhai
Abstract: A reciprocity electromagnetically induced transparency (EIT) effect can be obtained in the complementary graphene metasurface structure. The EIT spectra can be obtained whether the excitation was input from a positive or reverse direction. The transmission of the structure which consisted of a graphene square (GS) and the graphene circle of hollowed air square (GCHAS) placed on the top and bottom of the polyimide layer was discussed. A wideband EIT window was found in the structure of GCHAS as bright mode and GS as dark mode by the finite integration time domain method. The EIT effect can be tuned by the chemical potential, the electron-phonon relaxation time of graphene, and the widths of GCHAS and GS, respectively. The polarization insensitive EIT effect can be obtained. The transmission mechanism is interpreted by giving the electric and magnetic field distributions at certain frequencies. The effective permittivity of the structure was calculated by method of inversion. These results can be applied for many areas, such as wideband wavelength slow-light devices, active plasmon switching and bidirectional devices.